ANALISIS PENGARUH BIAYA KEAGENAN, RISIKO, PELUANG INVESTASI, DAN HUTANG TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN DI BURSA EFEK INDONESIA - Kusumawardani, Daning (STEKOM, 2011)
In the point of view of financial management, the aim of enterprise is maximize its value. Dividend isoften used by financier as indicator of enterprise prospect. Therefore, the enterprise need to pay attention onsome factors can influence the policy of dividend such is agency cost, risks, investment opportunity, andobligation in order to maximize value of the enterprise. This study analyze the influence of agency cost, risks,investment opportunity, and debt to the dividend policy in enterprise in Jakarta Stock Exchange. Data isobtained from secondary source on Indonesian Capital Market Directory (ICMD) and Indonesian StockExchange (IDX) of year 2005 â 2007. Hypothesis are analyzed with Linear Probability Model (LPM)Regression. Results of this study show that there are significant positive influence on INST variable to DPR,there area significant negative influence on GROW variable to DPR, no significant influence on Betavariable and DER variable to DPR. 40,3% of DPR Variable variation can be explained by INST, BETA,GROW, and DER variables, while the remain of 59,7% explained by other variables out of model. Fcount of8,767 with value of sig.0,000 means that variable INST, BETA, GROW, and DER collectively influence toDPR.Keywords: Agency cost, risks, investment opportunity, debt, dividend policy.